KAJIAN FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA DAN KESEJAHTERAAN MASYARAKAT DI PROVINSI BALI - Candri, Ketut; Bendesa, I Komang Gde (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
Bali is an island where tourism plays a dominant role in its economy, so its potential needs to be further developed. The purpose of this study is to analyze the effect of tourist visits, number of hotels, and hotel occupancy rates on total employment and welfare of the people in Bali . The data used is secondary data published by Bali Provincial Tourism Office and the Bali Province Central Statistics Agency from 2000-2019. The analysis technique used is path analysis. The results showed that the number of tourist visits has a positive and significant effect on total employment, the number of hotels has a negative and insignificant effect on total employment, while the hotel occupancy rate has a positive and insignificant effect on total employment. In addition, the number of tourist visits has a negative and insignificant effect on welfare, the number of hotels and the total employment have a positive and significant effect on welfare, while the hotel occupancy rate has a negative and significant effect on the welfare of the community.  Labor absorption is not a mediating variable between tourist visits and occupancy rate on welfare .